Perancangan dan Implementasi Sistem Keamanan Kendaraan dengan Teknologi Near Field Communication (NFC) - Subowo, Akbar Hadi; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
In modern times like now and at this time, motorcycle transportation is a necessity that cannot be avoided because the price of motorbikes is relatively cheap and affordable, including low service fees, making motorbikes used for daily transportation. with affordable prices and relatively cheap vehicle security systems by relying on handlebar locks and or padlocks are still not safe enough because the theft perpetrators can easily break into vehicle keys very quickly. iron-melting chemical liquid to melt the vehicle ignition key cover. With the increase in theft by motorized vehicles from year to year, this research will design a tool using near field communication with the main processor, namely Arduino Nano as the key. addition to vehicle contacts. The way this tool works is when the contact is on, the user will scan/tap the card when it is validated and has been registered, the relay will connect to the motorcycle ignition and if the card is not scanned or the card is not registered and relays will cut off the ignition on the motorbike. The design method applied is the waterfall. With this research, it is able to reduce the occurrence of vehicle theft and motorbikes are difficult to steal when parked.